The Effect of Modified Volkraw Games on the Learning Outcomes of Fifth Grade Elementary School Students - Lukman Firmansyah; Agung Wahyudi (Universitas Negeri Semarang, 2026)
The study was motivated by the low ability of students to perform basic volleyball skills, especially the underhand pass, which is influenced by a learning process that tends to be less varied and less engaging. Therefore, an innovation in learning is needed through simpler and more enjoyable game modifications suited to elementary school students. This study aims to examine the effect of modified Volkraw games on the learning outcomes of fifth-grade students at Sekaran State Elementary School 02 in Physical Education, particularly in volleyball material. This research employed a quantitative experimental approach using a one-group pretest–posttest design. The participants consisted of 20 fifth-grade students of Sekaran State Elementary School 02. The instrument used was a learning outcomes assessment sheet covering psychomotor, cognitive, and affective aspects. Data were collected through tests and observations, then analyzed using IBM SPSS Statistics, including normality and homogeneity tests, as well as hypothesis testing with a paired-samples t-test. The results showed that the average pretest score was 20.90, which increased to 32.20 in the posttest. The paired-samples t-test produced a significance value of 0.000 (p < 0.05), indicating that the modification of the Volkraw game had a significant effect on students’ learning outcomes. Based on these findings, it can be concluded that the implementation of modified Volkraw games is effective in improving volleyball learning.